THE ROLE OF RAW MATERIALS AND TECHNOLOGICAL EQUIPMENT IN KNITTING PRODUCTION (European Journal of Interdisciplinary Research and Development, 2026)
The knitting industry is a relevant branch of light industry, in which elastic, comfortable fabrics are produced based on natural and synthetic fibers [1] [2] . The article analyzes the types of raw materials (cotton, wool, synthetic fibers) in the production of knitwear and their properties. Also, the technical indicators, efficiency and efficiency of technological equipment such as flat and circular knitting machines are compared with numerical parameters. Modern equipment and materials are studied using examples of best practices in the world and Uzbekistan. Based on the results obtained, scientific and practical recommendations are given on the effective use of cotton and other fibers, the introduction of automated knitting technologies.